Bioavailability of selenium in soil-plant system and a regulatory approach. Issue 6 (19th March 2019) - Dinh, Quang Toan; Wang, Mengke; Tran, Thi Anh Thu; Zhou, Fei; Wang, Dan; Zhai, Hui; Peng, Qin; Xue, Mingyue; Du, Zekun; Bañuelos, Gary S.; Lin, Zhi-Qing; Liang, Dongli
Abstract: Understanding the bioavailability of selenium (Se) in the soil–plant system plays a vital role in phytoremediation and agronomic biofortification strategies. This review aimed to (a) discuss the effect of various soil parameters on the bioavailability of Se, its uptake and translocation in relation to plant species, genotypes, growth stages, and management regimes; and (b) examine soil and plant indices associated with Se bioavailability. In addition, we particularly discussed potential methods for regulating the bioavailability of Se. Such methods include the application of agricultural residue, Se fertilizer, or take advantage of the interaction between Se and other nutrient elements.